Criminality and Social Structure in Takeshi Kitano’s Outrage: A Sociological Approach - Seruni, Ayu putri; Filzarifadly, Muhammad (Chi e Journal of Japanese Learning and Teaching, 2025)
This study examines the representation of criminality in Takeshi Kitano’s Outrage through a sociological approach to literature, drawing on Willem Adriaan Bonger’s theory of criminal forms. Using a descriptive qualitative method, data were collected through observation and documentation, focusing on dialogues and scenes that depict economic, sexual, aggressive, and political dimensions of crime. The analysis also explores the underlying social factors that drive these forms of criminality. The findings reveal that Outrage portrays not only physical and psychological violence within the yakuza hierarchy but also fraud, extortion, and manipulation as systemic features of organized crime. These criminal forms are interrelated and serve as reflections of broader social inequalities. Viewed through the lens of literary sociology, the film represents a critique of Japan’s hierarchical and profit-driven society, where criminal behavior emerges as a response to structural injustice and social competition. Overall, this research demonstrates that Outrage functions as a mirror of social reality depicting criminality as both a personal and institutional phenomenon rooted in unequal power relations and sustained cycles of retribution.